Vigilancia monitoreable por medio de camaras IP con motor de seguimiento en el Colegio Raymundo Aveiga de la ciudad de Chone - Zambrano Cedeño, Edgar Eduardo (2013)
This thesis has as main objective the implementation of camera located in strategic areas allowing efficiently control entry to authorized personnel offices or not these areas as well as leakage of students in the particular area of Chone Aveiga Raymundo College. In order to analyze and identify the action that gives movement to the camera by sensor was used cascading method allows the use of necessary phases of the methodology. Wireless IP cameras were installed, two of which carry a motion sensor as they are located in areas where various departments and areas of leakage, these are connected to the school network, as also with a server where every move will be taxing cameras. The surveillance system using IP cameras made it possible to decrease the leak of students while controlling the entry of malicious person to different administrative departments , the reports that are generated are stored in a server's local disk which information may be revised to 1 month have been recorded.